Sports bra restriction on respiratory mechanics during exercise - Kipp, S.; Leahy, M. G.; Sheel, A. W. (Medicine & Science in Sports & Exercise, 2024)
Women perform exercise in sports bras to limit breast motion. However, as the breasts become restricted, respiratory function may become compromised.